An assessment of daylighting potential in Shanghai - Ni, Ming; Surapong Chiraratananon; Bhattacharya, Sribas C.; Supachart C.; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1993)
This study propose a design procedure for daylighting based on the use of a set of daylight factor curves produced for typical perimeter zones in Shanghai Goods and Materials Trade Center (SGMTC) building with its windows. The cases considered include perimeter zones with different window/ wall ratio in 6 compass derived from proposed radiation records of three years in Shanghai (1990, 1991, 1992). The procedure is also applied to a case study building. Physical measurement were performed and the results were analyzed and presented. Statistical frequency distribution of exterior horizontal dayliight illumination values are used to stratify illumination levels for use in conjunction with the daylight factor curves to determine the supplementary artificial light required to satisfy a given lighting requirement . We use two typical full day data (summer and winter) and the sample room which is a 7 x 7 m Module of SGMTC building as a project. From these data, we can get the results in 8 directions in SGMTC building on the daylighting vs energy use and the thermal heat gain or loss.
Thesis (M.Eng.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering.
Keywords: Daylighting -- China -- Shanghai